Estimating Fe and Mg Abundances in the Milky Way Dwarf Galaxies Using Subaru/HSC and DEIMOS - Jihye Hong; Evan N. Kirby; Tiffany M. Tang; Masashi Chiba; Yutaka Komiyama; Lauren E. Henderson; Itsuki Ogami; Timothy C. Beers (The Astrophysical Journal, 2025)
We investigate the chemical abundance distributions of the Fornax, Sculptor, Ursa Minor, and Draco dwarf galaxies using Subaru/Hyper Suprime-Cam (HSC) photometric data. The HSC data set, which includes broadband g and i filters and the narrowband NB515 filter, offers sensitivity to iron and magnesium abundances, as well as surface gravity, enabling the identification of giant stars and foreground dwarfs. For analysis, we selected a total of 6713 giant candidates using a random forest regressor trained on medium-resolution ( R ∼ 6000) Keck/Deep Imaging Multi-Object Spectrograph spectroscopic data. Our analysis reveals the extent of radial metallicity gradients in the galaxies. Such trends, not detectable in earlier studies, are now captured owing to the substantially enlarged sample size and areal coverage provided by the HSC data. These results are also consistent with chemical abundance patterns previously observed in the central regions through spectroscopic studies. Furthermore, we infer that Fornax underwent extended star formation, whereas Sculptor formed both metal-poor and metal-rich stars over a shorter time. Ursa Minor and Draco appear to have experienced brief, intense star formation episodes leading to nearly extinguished star formation. This study underscores the critical role of the expanded HSC data set in revealing chemical gradients that were previously inaccessible. Future work incorporating additional spectra of metal-poor stars and age-sensitive isochrone modeling will enable more accurate maps of chemical abundance distributions.